Double Retinal Tamponade for Treatment of Rhegmatogenous Retinal Detachment with Proliferative Vitreoretinopathy and Inferior Breaks - Mohamed Farouk Abdelkader; Shaaban Abd-Elhamid Mehany Elwan; Ahmed Shawkat Abdelhalim (Journal of Ophthalmology)
Purpose. To evaluate the efficacy and safety of the simultaneous use of short-term perfluoro-n-octane (PFO) with perfluoropropane (C3F8) gas to achieve retinal reattachment in eyes with rhegmatogenous retinal detachment (RRD) with proliferative vitreoretinopathy (PVR) grade C and multiple retinal breaks including inferior breaks. Design. This is a prospective interventional case series study. Patients and Methods. The study was a prospective noncomparative interventional study. It included 30 eyes of 30 patients who had RRD with PVR grade C and multiple retinal breaks including inferior tears attending the vitreoretinal unit of Minia University Hospital, Egypt. The mean age was 50.2 ± 10.63 years; 18 patients were females and 12 were males. Combined phacoemulsification and 23 G pars plana vitrectomy (PPV) with double retinal tamponade by C3F8 and PFO were done, and PFO was removed in 10–14 days. The patients were followed up for one year. The primary outcome was to achieve successful retinal reattachment, and the secondary outcomes were visual improvement and occurrence of complications. Results. Successful retinal reattachment was obtained in 28 eyes out of 30 (93.3%), and 2 eyes (6.7%) had recurrent RD. Best-corrected distance visual acuity (BCDVA) in logMAR was significantly improved from baseline 1.74 ± 0.05 to 0.93 ± 0.04, 0.82 ± 0.05, 0.80 ± 0.07, and 0.73 ± 0.055 at follow-up visits 3, 6, and 9 months and one year, respectively (P≤0.001). There were no serious ocular complications recorded. Conclusions. The results of this study indicated that primary vitrectomy with simultaneous use of both C3F8 and short-term PFO as retinal tamponades was effective and safe in the management of complex cases of RRD with PVR grade C and inferior breaks. This trial is registered with NCT04168255.